Childhood Trauma, Cognitive Emotion Regulation and Motivation for Behavior Change Among Clients of Opioid Substitution Treatment With and Without Past Year Synthetic Cathinone Use During Therapy - Kapitány-Fövény, Máté; Kiss, Anna; Farkas, Judit; Kuczora, Kinga Edit; Pataki, Patrícia; Horváth, Janka; Demetrovics, Zsolt (Frontiers in Neuroscience, 2020)
Background: With a decrease in heroin’s purity and availability in the European drug market, Hungarian opioid dependent patients started to substitute heroin with novel psychoactive substances (NPS) and especially with synthetic cathinones. Goal: This study aims to assess whether clients of opioid substitution treatment (OST) with and without a history of synthetic cathinone use during therapy differ in 1) the rate and type of experienced childhood trauma, 2) the way they cope with negative life events, 3) their motivation to change substance use behavior, 4) the rate of treatment retention. Methods: 198 clients of an outpatient centre’s (Nyírő Gyula National Institute of Psychiatry and Addictions, Budapest) OST were asked to provide information about their general substance use experiences, including the consumption of NPS during treatment, their childhood traumatic experiences (Childhood Trauma Questionnaire), cognitive emotion regulation strategies (Cognitive Emotion Regulation Questionnaire), their motivation to change substance use behavior (University of Rhode Island Change Assessment Scale) and current psychiatric symptoms (Brief Symptom Inventory). Baseline data was collected in the summer of 2015, while 4 years follow-up data on treatment retention was obtained in the summer of 2019. Results: The majority of the clients were male (N=141, 71.2%), receiving methadone as a substitute for opioids (N= 178, 89.9%), while mean age of the full sample was 39.7 (SD= 6.8). Based on a logistic regression model, the odds for past year synthetic cathinone use was higher among clients with more severe psychiatric symptoms (B=0.8, O.R. = 2.2, p<0.01) and among clients who were in treatment for a shorter period of time (B=0.1, O.R.= 0.9, p<0.05). Synthetic cathinone use during treatment was further associated with less adaptive strategies to cope with negative life events. Synthetic cathinone use was also a risk factor for reduced treatment retention (B= -0.8, O.R. = 0.4, p<0.05), associated with lower odds of being member of a latent class with less severe psychopathological profile (B= -0.9, O.R. = 0.4, p<0.05). Conclusion: Synthetic cathinone use during treatment is associated with poorer treatment outcomes and might be characterized by more severe psychiatric symptoms and amotivation to change substance use among opioid dependent clients.